Mechanically induced self-propagating reaction of vanadium carbonitride. Issue 3 (April 2015) - Roldán, M.A.; Alcalá, M.D.; Real, C.
Abstract: Vanadium carbonitrides (VC x N1− x ) were prepared via mechanosynthesis from mixtures of elemental vanadium and carbon with different V/C atomic ratios under a nitrogen atmosphere using a high-energy ball mill. We obtained the full composition range of carbonitrides at room temperature. The products were characterized using X-ray diffraction, scanning electron microscopy and electron energy loss spectroscopy. The results showed particle-sized products with high sinterability and very high microhardness.